The Influences Of Empathy, Depression, Anxiety And Stress On Supernatural Belief In Watching Horror Movies - Che Ab Adziz, Aselawati; Hashim, Rohani; Mustafa, Hasrina (2015)
This decade, a horror movie in the world is very encouraging. Apparently horror film has received much attention of the audience in Malaysia. Based on the collection of films box-office, it turns horror movie has got the attention of the audience in Malaysia. This genre does not only give pleasure even he touched the feelings and emotions of the audience and reflect real life, entertaining and inspirational. Therefore, this paper is to investigate the influence of psychological factors such as empathy, stress, depression and anxiety (DASS 21) against the supernatural beliefs. This study uses the Disposition Theory and Theory of Suspense of Enjoyment by Zillmann. This study evaluated the effectiveness and processes viewing pleasure as well as the belief in the supernatural. This paper presents the results of a pilot study of the items of Empathy, Depression, Anxiety, Stress and Supernatural Belief. This study was conducted in Jitra Mall Cineplex Cinema after they was watching the Film of Villa Nabila in January 2015.